2015
DOI: 10.1007/s11252-015-0515-z
|View full text |Cite
|
Sign up to set email alerts
|

Do trees flower longer in the city? A comparison of flowering eucalyptus trees in streets, remnants and continuous forest and their association with nectarivorous birds

Abstract: Human-dominated environments are often subjected to increased nutrient and moisture regimes which have the potential to influence the flowering phenology of plants. Protracted flowering periods within urban landscapes may result in increased food resources, in the form of nectar, and this high resource availability may support a high density of nectarivorous birds within cities. In order to determine whether there was a difference in the productivity and flowering period associated with urbanisation, we compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…For instance, the most abundant butterfly species in our surveys, common grass blues (GB), readily use the introduced white clover ( Trifolium repens ), one of the three most abundant species in our floral abundance surveys, as a larval host plant. In terms of adult food resources, the primarily native flowering plants in remnants and natural areas tend to have a short flowering periods in contrast to the much longer flowering periods of the mostly ornamental plants found in suburban and urban areas (Neil and Wu 2006, Leong and Roderick 2015, Davis et al 2016). This can perhaps limit the importance of remnant habitats because some of the resources they provide occur elsewhere within the urban environment.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, the most abundant butterfly species in our surveys, common grass blues (GB), readily use the introduced white clover ( Trifolium repens ), one of the three most abundant species in our floral abundance surveys, as a larval host plant. In terms of adult food resources, the primarily native flowering plants in remnants and natural areas tend to have a short flowering periods in contrast to the much longer flowering periods of the mostly ornamental plants found in suburban and urban areas (Neil and Wu 2006, Leong and Roderick 2015, Davis et al 2016). This can perhaps limit the importance of remnant habitats because some of the resources they provide occur elsewhere within the urban environment.…”
Section: Discussionmentioning
confidence: 97%
“…Gorton, Moeller & Tiffin (2018) found that the plant Ambrosia artemissifolia flowered earlier in urban than in rural habitats of Minneapolis (USA), and attributed this asynchronous flowering to genetic differences between populations. On the other hand, Davis, Major & Taylor (2016) found that native trees in Sydney (Australia) flowered longer in streets than in remnant and continuous forests, providing more food resources to nectarivorous birds. Nectar and fruits may be available during seasons when they would be naturally absent or scarce due to the planting of ornamental trees (Williams & Karl, 1996; Corlett, 2005; Leston & Rodewald, 2006; Williams et al, 2006; Montaldo, 1984; Leveau, 2008; Leveau & Leveau, 2011; Davis, Major & Taylor, 2015; Gray & Van Heezik, 2016) (Fig.…”
Section: Temporal Stabilization Of Resources and Habitatsmentioning
confidence: 99%
“…On the other hand, Davis et al (2016) found that native trees in Sydney (Australia) flowered longer in streets than in remnant and continuous forests, providing more food resources to nectarivorous birds. Nectar and fruits may be available during seasons when they would be naturally absent or scarce due to the planting of ornamental trees (Williams and Karl, 1996;Corlett, 2005;Leston and Rodewald, 2006;Williams et al, 2006;Montaldo, 1984;Leveau, 2008;Leveau and Leveau, 2011;Davis et al, 2015;Gray and van Heezik, 2016) (Figure 1).…”
Section: Biotic Factorsmentioning
confidence: 99%